Hospitality and catering for GCSE - Gardiner, Judy; Housley, Jacqui (United Kingdom : Hodder Education, 2009)
Completely revised and updated for WJEC's new courses in GCSE Hospitality and Catering, this book is designed to support students throughout their study, coursework preparation and revision for final exams. The book is packed with all the information that students will need for the course and has been expanded to provide more knowledge in some key areas. All the information is presented in a colourful, uncomplicated and concise fashion. It is illustrated with photos and cartoons throughout, bringing the subject alive, as well as hands-on activities and revision questions to ensure your study.
Chapter 1. GCSE Catering (single award) -- Chapter 2. Assessment for GCSE Catering (single award) -- Chapter 3. GCSE Hospitality (single award) -- Chapter 4. Assessment for GCSE Hospitality (single award) -- Chapter 5. Hospitality and catering examination questions and answers
Includes index.
Keywords: HOSPITALITY INDUSTRY -- EMPLOYEES -- TRAINING OF -- GREAT BRITAIN